A inconstitucionalidade de Belo Monte sob a perspectiva dos direitos indígenas dos povos Arara do Maia e Juruna do Paquiçamba - XERFAN, Renato da Cruz (Universidade Federal do Pará, 2018)
The implementation of the Hydroelectric Power Plant Belo Monte operates numerous battles that occurs in different fields, such as environmental, legal, economic, political and cultural. This study, using the hypothetical deductive method and bibliographic, documentary, and field research, aims to identify possible unconstitutionalities in the development of this project that seeks to change drastically the water regime of the mediun/ lower course of one of the main tributaries of the Amazon: the Xingu river. We analyze whether the work in question is in accordance with environmental and multicultural perspective dashed by the Constitution of the Federative Republic of Brazil in 1988 and numerous international agreements and declarations taking a cut on water management in the Amazon and its correlation with environmental law, seen from an ecological and systemic perspective of the cultural rights of indigenous peoples directly affected by the project. Giving up will attention to the situation of people Arara of the Volta Grande (Maia Arara) and Juruna (Yudjá) of Paquiçamba that are included in the area of direct influence of the work, the Volta Grande do Xingu, which suffers losses of about 80 % water resources that once flowed freely through the natural river bed with shocking losses to the traditional way of life of the people of the forest and the lush biodiversity of the region. In this endeavor we analyze the judicial struggle led to the cable by Ministério Público Federal (Brazilian Government Agency for Law Enforcement) with particular attention to actions brought by the Parquet to promote the observance and respect for indigenous rights. The study also reflects on the rights of Nature and Future Generations, understanding them as members of the subjective framework of the rights of indigenous peoples of the Xingu who create and recreate themselves in the multiplicity of the components of biodiversity. Seek, ultimately, to identify whether that energy development is in harmony with the norms and values advocated by the Brazilian and international legal and political system enshrining the Brazilian State must, by promoting democratic policies and honoring the multiple use of water, be the guarantor of the perpetuation and maintenance of Amazonian indigenous cultures and healthy environment.